Zn(II) 5, 5‐Diethylbarbiturate Complex Selectively Induces Apoptosis in Breast Cancer and Breast Cancer Stem‐Like Cells. Issue 4 (21st March 2022) - Alioglu, Imren; Tsochantaridis, Ilias; Pappa, Aglaia; Dere, Egemen; Ari, Ferda
Abstract: The biological activities of Zn(II) compounds have been extensively studied in recent years. In this study, the growth suppressive effect of Zn(II) 5, 5‐diethylbarbiturate complex on MCF‐7 and MDA‐MB‐231 human breast cancer cells was determined by SRB and ATP viability assays and apoptosis‐inducing effect by double staining method. Significant increase in cytokeratin 18 level, caspase 3/7 activity and annexin‐V upregulation prove that Zn(II) complex has apoptotic effect in breast cancer cells. Intrinsic apoptosis pathway in MCF‐7 cells and extrinsic apoptosis pathway in MDA‐MB‐231 cells was determined by Western blot (PARP, Cleave PARP, BAX, COX4, RIP, Caspase 8, Split Caspase 8, DR4 and B‐Actin) and RT‐PCR (PARP, Fas, Bcl‐2, TNF10A, P53) analysis. No reduction of viability was found in MCF‐710A healthy breast cells treated with Zn(II) complex. In breast cancer stem‐like cells (MCF‐7s), the Zn(II) complex was found to have a cytotoxic effect and to activate the apoptotic pathway. As a result, it was concluded that Zn(II) complex has anti‐proliferative and apoptotic effects on breast cancer and breast cancer stem‐like cells. Also this complex prevents the metastatic effect of cancer cells and does not effect to healthy cells so this complex has a specific effect on cancer cells. These findings might shed light on the discovery of new chemotherapeutic agents. Abstract :